THE ASSISTANT FACTORS OF MUSEUM EXHIBITION - Nuraliyeva Munira Faxritdinovna (The Conference Hub, 2025)
This article explores the essential assistant factors that contribute to the success of museum exhibitions, such as curatorial support, exhibition design, technical installation, educational services, and visitor assistance. Drawing on scholarly opinions and recent studies, the paper emphasizes the importance of teamwork and behind-the-scenes roles in creating engaging and educational museum experiences.